On the way to 2020: data for vocational education and training policies : country statistical overviews - (:unkn) unknown (Publications Office of the European Union, 2015)
"European policy-making in vocational education and training (VET) needs to be supported by sound evidence. In this report, Cedefop has selected a set of 33 indicators to quantify some key aspects of VET and lifelong learning. The selection is based on the indicators’ policy relevance and their importance in achieving the Europe 2020 objectives. This publication should be regarded as a valuable tool to help policy-makers better understand and assess VET developments in each country. The report includes recent evidence from the European Statistical System. While this set of indicators does not claim to assess national systems or policies, they could be used to reflect on progress towards the strategic objectives set for Europe. The indicators take 2010 as the baseline year and present statistical overviews in all European Union Member States and also the former Yugoslav Republic of Macedonia, Iceland, Norway, Switzerland and Turkey." (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; T 3.5 Statistik; I 2.2 Europa; Berufsbildungssystem; Monitoring; Indikatoren; Europa; Türkei